Congestive heart failure and converting enzyme inhibition: failure of current prognostic criteria for predicting subsequent renal insufficiency. Issue 786 (April 1991) - Odum, J.; Carson, P.; Russell, G.
Abstract : Angiotensin-1-converting enzyme inhibitors have an effective and established role in the treatment of patients with congestive heart failure. However, a small number of such patients will subsequently develop renal insufficiency. These patients may be identified prior to, or shortly after, commencement of therapy by recognized criteria. This report describes 4 patients with congestive heart failure who developed severe renal insufficiency secondary to either enalapril or captopril therapy in the absence of any currently recognized predisposing factors. One patient died.